2010
DOI: 10.1016/j.ejpain.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and testosterone differently affect visceral pain‐related behavioural responses in male and female rats

Abstract: In the study of pain, the presence of sex differences is well known, with female subjects being more affected in a number of chronic painful conditions; however, the underlying mechanisms and the involvement of gonadal hormones, are still controversial. This study evaluated visceral pain in a validated rat model of artificial calculosis and the effects of estradiol and testosterone administration. Adult male and female rats were divided into groups and treated with one of the substances or Oil (vehicle) for 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 35 publications
(39 reference statements)
0
37
0
1
Order By: Relevance
“…The effects of estrogens on nociception are bimodal being both pronociceptive as well as antinociceptive. Antinociceptive actions of estrogens include: (1) KOR antinociception and gene expression are enhanced by exogenous or endogenous estradiol in female [102], (2) long term (28 days) ovariectomy of adult rats induces thermal and mechanical hyperalgesia that can be reversed by estradiol replacement [169], (3) physiological concentrations of estradiol attenuate drug-induced temporomandibular joint (TMJ) pain [71,96], (4) in a rat model of calculosis, estradiol is an effective analgesic in females but not males [6], (5) in women, the follicular phase (elevated estradiol) has been associated with higher thresholds to pressure, thermal and ischemic muscle pain than later phases [162], which is consonant with studies in rats showing enhanced uretal pain sensitivity during metestrus / diestrus vs. proestrus / estrus [77]. These findings agree with reports of a greater incidence of colics in the perimenstrual period (equivalent to metestrus and diestrus in rats) in fertile women with urinary calculosis.…”
Section: Ovarian Sex Steroids and Nociception/antinociceptionmentioning
confidence: 99%
“…The effects of estrogens on nociception are bimodal being both pronociceptive as well as antinociceptive. Antinociceptive actions of estrogens include: (1) KOR antinociception and gene expression are enhanced by exogenous or endogenous estradiol in female [102], (2) long term (28 days) ovariectomy of adult rats induces thermal and mechanical hyperalgesia that can be reversed by estradiol replacement [169], (3) physiological concentrations of estradiol attenuate drug-induced temporomandibular joint (TMJ) pain [71,96], (4) in a rat model of calculosis, estradiol is an effective analgesic in females but not males [6], (5) in women, the follicular phase (elevated estradiol) has been associated with higher thresholds to pressure, thermal and ischemic muscle pain than later phases [162], which is consonant with studies in rats showing enhanced uretal pain sensitivity during metestrus / diestrus vs. proestrus / estrus [77]. These findings agree with reports of a greater incidence of colics in the perimenstrual period (equivalent to metestrus and diestrus in rats) in fertile women with urinary calculosis.…”
Section: Ovarian Sex Steroids and Nociception/antinociceptionmentioning
confidence: 99%
“…Notably, in female rats, 17-β-estradiol (estradiol), the predominant estrogen, can be pronociceptive [12; 43; 44; 60; 65; 88], as well as antinociceptive [4; 15; 32; 34; 50; 55; 66; 84; 89]. Modulation of nociception/opioid antinociception by estrogens occurs, in part, via classical nuclear estrogen receptors (ERs), which function as estrogen-activated transcription factors [21].…”
Section: Introductionmentioning
confidence: 99%
“…27 In the field of visceral responses, most of the preclinical studies conducted were in male rodents, 37 but few studies in females indicated that sex hormones may have an effect on visceral sensitivity in rodents. 38,39 Some studies did not even mention the sex of experimental rodents. 33 The use of a balanced proportion of male and female rodents in preclinical studies and application of sex-based analysis are needed to elucidate sex-related differences in the pathophysiological mechanism of IBS.…”
mentioning
confidence: 99%